Efficacy and safety of perampanel as early add-on therapy in Chinese patients with focal-onset seizures: a multicenter, open-label, single-arm study - Gao, Lehong; Lu, Qiang; Wang, Zan; Yue, Wei; Wang, Guoping; Shao, Xiaoqiu; Guo, Yi; Yi, Yonghong; Hong, Zhen; Jiang, Yuwu; Xiao, Bo; Cui, Guiyun; et al. (Frontiers in Neurology, 2023)
Background No interventional study has been conducted in China to assess efficacy and safety of perampanel in treating Chinese patients with epilepsy, nor has there been any study on perampanel early add-on therapy in China. This interventional study aimed to assess efficacy and safety of perampanel as an early add-on treatment of focal-onset seizures (FOS) with or without focal-to-bilateral tonic–clonic seizures (FBTCS) in Chinese patients. Methods In this multicenter, open-label, single-arm, phase 4 interventional study, Chinese patients ≥ 12 years old with FOS with or without FBTCS who failed anti-seizure medication (ASM) monotherapy from 15 hospitals in China were enrolled and treated with perampanel add-on therapy (8-week titration followed by 24-week maintenance). The primary endpoint was 50% responder rate. Secondary endpoints included seizure-freedom rate and changes in seizure frequency from baseline. Treatment-emergent adverse events (TEAEs) and drug-related TEAEs were recorded. Results The full analysis set included 150 patients. The mean maintenance perampanel dose was 5.9 ± 1.5 mg/day and the 8-month retention rate was 72%. The 50% responder rate and seizure-freedom rate for all patients during maintenance were 67.9 and 30.5%, respectively. Patients with FBTCS had higher 50% responder rate (96.0%) and seizure-freedom rate (76.0%) during maintenance. Patients on concomitant sodium valproate had a significantly higher seizure-freedom rate than those on concomitant oxcarbazepine. Eight-six (55.1%) patients experienced treatment-related TEAEs, and the most common TEAEs were dizziness (36.5%), hypersomnia (11.5%), headache (3.9%), somnolence (3.2%), and irritability (3.2%). Withdrawal due to TEAEs occurred to 14.7% of the patients. Conclusion Perampanel early add-on was effective and safe in treating Chinese patients≥12 years old with FOS with or without FBTCS. Clinical trial registrationwww.chictr.org.cn, Identifier ChiCTR2000039510.